Analisis Pengaruh Faktor Pengetahuan, Peran Petugas Kesehatan dan Dukungan Keluarga Terhadap Keaktifan Pemanfaatan Prolanis di Wilayah Kerja Puskesmas Balen Kabupaten Bojonegoro - Niken Mastiko Rahayu; Henry Sudiyanto; Dhonna Anggreni (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2025)
Chronic diseases are a global health problem affecting physical health and overall quality of life. The National Health Insurance Agency (BPJS Kesehatan) launched the Chronic Disease Management Program (Prolanis) to provide continuous healthcare for participants with chronic diseases. In East Java, Prolanis achievement decreased from 49.65% in 2023 to 42.46% in 2024. This study aimed to analyze the influence of knowledge, the role of health workers, and family support on Prolanis utilization activeness in Balen Public Health Center, Bojonegoro Regency. This cross-sectional study used simple random sampling involving 154 respondents. Data were collected through questionnaires and analyzed using chi-square tests (α = 0.05) and logistic regression. Results showed respondents with good knowledge were 50.6%, positive perceptions of health workers 51.3%, family support 53.2%, and active Prolanis utilization 53.9%. Statistical tests revealed the influence of knowledge (p = 0.000), the role of health workers (p = 0.000), and family support (p = 0.000) on activeness. Logistic regression indicated knowledge (OR = 31.899) as the most influential factor, followed by the role of health workers (OR = 9.121). It is concluded that knowledge, the role of health workers, and family support can improve participation in Prolanis to enhance health, quality of life.